Diplomasi Kuasi Mediasi Tiongkok dalam Menjembatani Penyelesaian Konflik Tigray dan Pemerintah Ethiopia Tahun 2020-2022 - Theresia Kariani Yolin; Indra Wisnu Wibisono; Roberto Octavianus Cornelis Seba (Pusat Riset dan Inovasi Nasional, 2025)
The Tigray conflict and the Ethiopian Government in 2020-2022 were mainly motivated by dissatisfaction with the policies of Prime Minister Abiy Ahmed. TPLF as a representative party of the Tigray ethnic group attacked the government until it received a counterattack that further prolonged the conflict situation. The conflict then sparked international attention, including China. China played a role in bridging the conflict resolution indirectly. This study aims to review the efforts made by China in helping to bridge the conflict resolution. The method used uses a descriptive qualitative approach. The study found that China fully used a quasi-mediation diplomacy strategy in an effort to resolve the conflict. China's efforts are reflected through personal identity and the results of the interactions that were established. China promotes the principle of non-intervention and regional resolution, even providing humanitarian assistance and sustainable development. China is not directly involved in maintaining national interests, both materially and socially, in the form of applicable relations and norms.